Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1002/kin.550210802
|View full text |Cite
|
Sign up to set email alerts
|

Rate constants for hydrogen abstraction reactions of the sulfate radical, SO4. Alkanes and ethers

Abstract: Rate constants have been determined for the reactions of SO4-with a series of alkanes and ethers. The SO, radical was produced by the laser-flash photolysis of persulfate, SZO: -.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(58 citation statements)
references
References 9 publications
3
54
1
Order By: Relevance
“…The reason for that difference is not clear, but in that study, in opposition to the other investigations, it was not a direct determination but the kinetics that were obtained relative to 1,3,5-trimethoxybenzene, which is very reactive compared to alcohols. So, we believe that for the same reason as described previously, our work is in agreement with the results reported by Huie and Clifton [22].…”
Section: ؉ Alcoholssupporting
confidence: 95%
See 1 more Smart Citation
“…The reason for that difference is not clear, but in that study, in opposition to the other investigations, it was not a direct determination but the kinetics that were obtained relative to 1,3,5-trimethoxybenzene, which is very reactive compared to alcohols. So, we believe that for the same reason as described previously, our work is in agreement with the results reported by Huie and Clifton [22].…”
Section: ؉ Alcoholssupporting
confidence: 95%
“…All the results are summarized in Table III . When compared to literature data (see Table III), the values for diethyl ether and tert-butyl methyl ether appear to be 20 -30% higher than the two other determinations [20,22] which have been conducted at room temperature (i.e., at a temperature 5 -10 K lower than in our study). This difference may certainly be the reason for this apparent difference.…”
Section: ؉ Alcoholscontrasting
confidence: 46%
“…Also, we found that the rate constant for the reaction of SO,-with p-dioxane is lower than for the reaction with tetrahydrofuran [7]. Assuming the C -H bonds a to the ether linkage are weaker than normal secondary C -H bonds, the reverse order of reactivity would be expected.…”
Section: Introductionmentioning
confidence: 77%
“…The sulfate radical anion is a strong oxidant in aqueous phase. For example, Huie and Clifton (1989) have reported that hydrogen abstraction by sulfate radical anions on the alkane can result in the formation of bisulfate ions. They also reported that the hydrogen 20 abstraction rate is the highest on the tertiary carbon, and the rate is one order of magnitude smaller for the secondary carbon, and even smaller for the primary carbon.…”
Section: Formation and Reaction Of Sulfate Radical Anion In The Oh Rementioning
confidence: 99%